Penerapan Metode K-Means Dalam Menentukan Klasifikasi Produk Pembelian Pelanggan - Kevin Noel Nababan (BEES: Bulletin of Electrical and Electronics Engineering, 2022)
According to the survey, there are approximately 3,500 types of food and non-food products available at competitive prices, meeting almost all the daily needs of consumers. With a fairly large number of transactions, companies need analysis and classification tools to provide useful information for companies in determining the layout of goods, what goods are most in demand by consumers and others. Determination of the layout of food and beverage products is carried out to make it easier for consumers to find food and beverage products so as not to disappoint consumers in finding the location of which products are suitabel to be combined with other products that are often in demand by consumers so that consumers can save time. Based on the description above, a data mining analysis tool is needed using Association Rules to be processed using the K-Means method. Currently, the utilization of the available data has not been maximized, it is only limited to making reports.